2019
DOI: 10.3389/fendo.2019.00662
|View full text |Cite
|
Sign up to set email alerts
|

Luteal Lipids Regulate Progesterone Production and May Modulate Immune Cell Function During the Estrous Cycle and Pregnancy

Abstract: Although the corpus luteum (CL) contains high concentrations of lipid in the form of steroid hormone precursors and prostaglandins, little is known about the abundance or function of other luteal lipid mediators. To address this, 79 lipid mediators were measured in bovine CL, using ultra performance liquid chromatography-tandem mass spectrometry. CL from estrous cycle days 4, 11, and 18 were compared and, separately, CL from days 18 of the estrous cycle and pregnancy were compared. Twenty-three lipids increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Despite indications that bioactive lipids have an important role in CL function ( Wiltbank & Ottobre 2003 , Hughes et al 2019 ), little is known about the function of specific luteal lipid mediators in this process, although luteal progesterone is clearly of utmost importance for pregnancy maintenance ( Allen 2001 ). Interestingly, pioneering studies first noted that circulating progesterone in mares, in comparison to many other species, was surprisingly low ( Short 1959 , Holtan et al 1979 ) and that 5α-reduced pregnanes including the sterol lipid 5α-dihydroprogesterone (DHP) were surprisingly high ( Holtan et al 1991 ).…”
Section: Exploration Of Lipid Pathways In Equine Cyclicity and Early ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite indications that bioactive lipids have an important role in CL function ( Wiltbank & Ottobre 2003 , Hughes et al 2019 ), little is known about the function of specific luteal lipid mediators in this process, although luteal progesterone is clearly of utmost importance for pregnancy maintenance ( Allen 2001 ). Interestingly, pioneering studies first noted that circulating progesterone in mares, in comparison to many other species, was surprisingly low ( Short 1959 , Holtan et al 1979 ) and that 5α-reduced pregnanes including the sterol lipid 5α-dihydroprogesterone (DHP) were surprisingly high ( Holtan et al 1991 ).…”
Section: Exploration Of Lipid Pathways In Equine Cyclicity and Early ...mentioning
confidence: 99%
“…In the cow, there have been reports that lipids ingested through dietary supplementation can alter the luteal response to PGF 2α ( Plewes et al 2018 ). A recent study in the dairy cow looked at in vitro lipidomic changes in the CL during MRP and suggested that lipids and mRNAs in the CL may regulate a suite of MRP-associated events, including immune cell chemotaxis and cell-cell communication ( Hughes et al 2019 ). Of particular interest was the eicosanoid 15-KETE, which is a major metabolite of AA.…”
Section: Exploration Of Lipid Pathways In Equine Cyclicity and Early ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Using targeted analysis approach, tremendous work has been done on understanding molecular regulation of CL biology. Several mechanisms and factors regulating luteal growth and regression are known that involve lipid metabolism in CL [ 8 , 9 ], angiogenesis [ 10 , 11 ] and apoptosis [ 12 , 13 , 14 ], extracellular matrix remodeling [ 15 ], immune-endocrine cross-talk [ 16 , 17 ], role of tumor necrosis factor alpha and macrophages [ 18 , 19 , 20 ], and enzymes involved in steroidogenesis [ 1 ]. The CL during the estrous cycle undergoes tremendous changes in its structure and function.…”
Section: Introductionmentioning
confidence: 99%
“…PGF 2α regulates development and function of the corpus luteum, and PGE 2 is increased during the late-luteal phase followed by a decrease during regression [ 3 ]. The production levels of lipid mediators such as 15-KETE and oxylipin in the corpus luteum of cows are altered as the estrous cycle progressed [ 16 ]. These studies indicate that PUFAs are involved in reproduction.…”
mentioning
confidence: 99%